Transcriptomic Pattern of Genes Regulating Protein Response and Status of Mitochondrial Activity Are Related to Oocyte Maturational Competence-A Transcriptomic Study - Chermuła, Błażej; Brązert, Maciej; Jeseta, Michal; Ożegowska, Katarzyna; Kocherova, Ievgenia; Jankowski, Maurycy; Celichowski, Piotr; Sujka-Kordowska, Patrycja; Konwerska, Aneta; Piotrowska-Kempisty, Hanna; Budna-Tukan, Joanna; Antosik, Paweł; et al. (International journal of molecular sciences, 2019)
This paper aims to identify and describe new genetic markers involved in the processes of protein expression and modification reflected in the change of mitochondrial activity before and after in vitro maturation of the oocyte. Porcine oocytes collected from the ovaries of slaughtered landrace gilts were subjected to the process of in vitro maturation. Transcriptomic changes in the expression profile of oocyte genes involved in response to hypoxia, the transmembrane protein receptor serine threonine kinase signaling pathway, the "transforming growth factor β receptor signaling pathway", "response to protein stimulus", and "response to organic substance" were investigated using microarrays. The expression values of these genes in oocytes was analyzed before (immature) and after (mature) in vitro maturation, with significant differences found. All the significantly altered genes showed downregulation after the maturation process. The most changed genes from these gene ontologies, FOS, ID2, VEGFA, BTG2, CYR61, ESR1, AR, TACR3, CCND2, CHRDL1, were chosen to be further validated, described and related to the literature. Additionally, the mitochondrial activity of the analyzed oocytes was measured using specific dyes. We found that the mitochondrial activity was higher before the maturation process. The analysis of these results and the available literature provides a novel insight on the processes that occur during in vitro oocyte maturation. While this knowledge may prove to be useful in further research of the procedures commonly associated with in vitro fertilization procedures, it serves mostly as a basic reference for further proteomic, in vivo, and clinical studies that are necessary to translate it into practical applications.
Keywords: prasata; Swine; transkriptom; oocyte maturation; Mitochondria; hypoxie buňky; oocyty; Transforming Growth Factor beta; IVM techniky; signální transdukce; Transcriptome; mitochondrial activity; Signal Transduction; transformující růstový faktor beta; kultivované buňky; oogeneze; microarray; Animals; ženské pohlaví; Cell Hypoxia; zvířata; tyrosinkinasové receptory; pig; Cells, Cultured; In Vitro Oocyte Maturation Techniques; Receptor Protein-Tyrosine Kinases; Female; mitochondrie; Oogenesis; Oocytes